2019 10th IEEE International Conference on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applicat 2019
DOI: 10.1109/idaacs.2019.8924296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Involving Students in Producing Learning Aids in Project Management. The Animation Project

Abstract: The purpose of this paper is to present the preliminary findings from implementing and evaluating a project-based learning example (The Animation Project). The idea of the project is to involve the students in producing learning aids in project management in the form of video animations of real-life project cases. This was done to create an authentic project experience of actual projects that has solutions that potentially could be implemented. The preliminary findings suggest that the project adequately satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They concluded that the academic achievement and retention of knowledge of project-based learning groups were better than those of a traditional teaching group. Hussein et al [32] showed that PjBL can be used for the co-creation of teaching and learning materials. Bovill et al [33] explained that the co-creation of learning and teaching occurs when staff and students work collaboratively with one another to create components of curricula and/or pedagogical approaches.…”
Section: Impact Of Pjblmentioning
confidence: 99%
“…They concluded that the academic achievement and retention of knowledge of project-based learning groups were better than those of a traditional teaching group. Hussein et al [32] showed that PjBL can be used for the co-creation of teaching and learning materials. Bovill et al [33] explained that the co-creation of learning and teaching occurs when staff and students work collaboratively with one another to create components of curricula and/or pedagogical approaches.…”
Section: Impact Of Pjblmentioning
confidence: 99%